Survey on diversity, relative abundance and hydrology of fishes in Ayima, Alatish and Gelegu Rivers, of Alatish National Park, Ethiopia - Dereje Tewabe (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2020)
Fish species of rivers Ayima, Alatish, and Gelegu were studied from samples collected by 6, 8, 10,12 and 14 cm stretched mesh size gillnet, monofilament of different mesh size, hook-lines, fykenet and castnet. The fishes were collected during October, 2008 to January, 2009. The samples were collected in the dry season and wet season. 20 fish species were identified from two rivers, but fish was not sampled from Alatish River due to its short lived seasonality, and these are included in the families Centropomidae, Cichlidae, Bagridae, Clariidae, Mochokidae, Osteoglossidae, Characidae, Citharinidae and Cyprinidae. A higher number of species was recorded from river Ayima with 20 species, whereas only two species were identified from Gelegu River. Fishing activities was destructive type, using plant poisoning materials, and chemicals (Malathion) which is non selective and dangerous for all biota.